Populists in power and conspiracy theories. (May 2023) - Pirro, Andrea LP; Taggart, Paul
The populist use of tropes such as conspiracy theories plays an increasingly important role in their politics. Populism and conspiracy theories present a number of common traits – Manichaeanism, a sense of victimhood, and an ambivalence towards representative politics – and populists' use of conspiracy theories is politically purposeful. Targeting a conspiring elite serves to vilify real or fictional opponents and/or shield populists from hostile attacks. Looking at three cases of populists in government – Orbán in Hungary, Trump in the United States, and Chávez in Venezuela – we examine the definition of conspiring elites (who), the circumstances under which conspiracy theories are propagated (when), and the ultimate purpose of conspiratorial framing (why). We demonstrate how populists in power use conspiracy theories to demonise and delegitimise their opponents, to promote or prolong a sense of crisis, and to rally support while distracting from possible failure.